Persediaan kerjaya pelajar tahun akhir diploma akauntansi Politeknik dalam melahirkan K-Workes : satu tinjauan - Wan Mohd Nowalid, Wan Marina (2003)
This research was conducted to identify Polytechnic's Diploma in Accountancy final year students' career preparation before enter the working environment to be k-workers. The sample in this study consisted of 48 final year students of Diploma in Accountancy Politeknik Sultan Haji Ahmad Shah (POLISAS), Kuantan. Questionnaire has been chosen as an instrument to get the data. The data was analyzed by using the Statistical Package For Social Sciences (SPSS) package to derive the percentages and mean. The results revealed the Diploma of Accountancy final year students are quite prepared to enter the working environment. Although the students performed very well for their career preparation, there are still dissatisfaction in other two aspects i.e. they lack of information career opportunity and communication in English. Therefore, the career guideline have been proposed to give an exposure for the students to be k-workers in their career in the future.